Gladstone Nigeria Limited. Business Plan For Investment in A Granite Quarry at Okene in Kogi State Nigeria. - Nkechika, Augustus (2015)
This Business Plan is being presented to an investor to enable additional funding of the sum of N250 million for the procurement of operational (working capital) items and get through the cash flow ''valley of death'' during the early periods of the business to enable accelerated growth. This funding is for a five year term. in return the investor gets a return of 5% convertible preference shares annually and a lump sum at 10% IRR at the end of year 5.